Pengaruh Terapi Bekam Terhadap Tekanan Darah Pada Pasien Hipertensi Di Pusat Terapi Bekam Lpk Lentera Jagat - Eldessa Vava Rilla; Dede Samarudin (STIKes Karsa Husada Garut, 2021)
Hypertension is caused by two factors, namely factors that can be controlled or controlled and factors that cannot be controlled or cannot be controlled. Factors that can be controlled or can be controlled are lifestyle factors, wrong diet, and excessive weight. While the factors that cannot be controlled or cannot be controlled are genetics, age, gender, and ethnicity (Susilo, 2013). Based on a preliminary study that has been carried out by researchers by interviewing 12 hypertensive patients at the LPK Lentera Jagat cupping therapy center, they have taken every means to lower their blood pressure, starting from taking traditional medicines, medicinal plants, and hypertension exercise, 8 people said there had been no significant change. significant reduction in blood pressure. The purpose of this study was to determine the effect of cupping therapy on blood pressure in hypertensive patients. This study used a quasi-experimental design with a pretest-posttest control group design approach. The sample used was 25 respondents. d. There was an effect of cupping therapy on blood pressure in hypertensive patients at the LPK Lentera Jagat Cupping Therapy Center which was statistically significant (p = 0.000 <0.05). This study found that cupping therapy given to hypertensive patients experienced a change, namely a decrease in blood pressure in systolic and diastolic. Cupping can be used as an alternative treatment for people who have hypertension to use cupping therapy on a regular basis